Dust. Semiotic Issues on Substances - Bassano , Giuditta (E|C, 2023)
This article explores the problem of materials with respect to contemporary semiotic research. The contribution defines a general problem of including processual aspects in the analysis of materials and artefacts. It therefore focuses on dust, as a material identified both in a socio-technological sense and focused on by many contemporary art works. In analyzing dust, a proposed model for the problems posed by materials is outlined, as including: a figurative dimension, a figural dimension, a thymic dimension, and an aspectual dimension. Some strengths and weaknesses of this proposal are discussed in the final part of the article.